Moebius Syndrome: A Rare Case Report - M Srinivasa Raju; G N Suma; Ravi Prakash; Sumit Goel (Wolters Kluwer Medknow Publications, 2011)
Moebius syndrome is an extremely rare disorder. Only approximately few hundred cases have been reported in literature. In a nationwide survey reported in 2003, the prevalence of this syndrome was at least 0.002% of births for the years 1996 to 1998. The definition and diagnostic criteria for Moebius syndrome vary among authors. In most studies, it is defined as congenital facial weakness combined with abnormal ocular abduction. The list of signs and symptoms mentioned in various sources for Moebius syndrome includes more than 20 peculiar features. Here, we report an interesting case of Moebius syndrome in a 12-year-old male patient with all the important peculiar signs and symptoms.